The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/hsc.12348
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transitional programmes on post-transition outcomes for youth leaving out-of-home care: a meta-analysis

Abstract: Youth residing in out‐of‐home care settings have often been exposed to childhood trauma, and commonly report experiencing adverse outcomes after transitioning from care. This meta‐analysis appraised internationally published literature investigating the impact of transitional programme participation (among youth with a baseline age of 15–24 years) on post‐transition outcomes of housing, education, employment, mental health and substance use. A comprehensive search of sociology (e.g. ProQuest Sociology), psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 42 publications
2
34
0
8
Order By: Relevance
“…Only a small proportion of studies found improvements in care-leavers' social support networks after engaging in the programme (Anglicare, 2016;Compass Leaving Care Limited, 2019;Mendes, 2011) and in mental health and substance misuse (Baldry et al, 2016). These findings are consistent with the international literature (Heerde et al, 2018;Woodgate et al, 2017) that found transitional support programmes to be less effective in improving health as compared to independent living outcomes. Whilst the majority of studies in this review (8/11) assessed the impact of the programme on a health-related outcome (e.g., mental health, social support, or physical health), the transition interventions themselves primarily aimed to assist young people to achieve indicators of independence (e.g., housing, employment), rather than specifically aiming to improve health outcomes, which may account for these findings.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Only a small proportion of studies found improvements in care-leavers' social support networks after engaging in the programme (Anglicare, 2016;Compass Leaving Care Limited, 2019;Mendes, 2011) and in mental health and substance misuse (Baldry et al, 2016). These findings are consistent with the international literature (Heerde et al, 2018;Woodgate et al, 2017) that found transitional support programmes to be less effective in improving health as compared to independent living outcomes. Whilst the majority of studies in this review (8/11) assessed the impact of the programme on a health-related outcome (e.g., mental health, social support, or physical health), the transition interventions themselves primarily aimed to assist young people to achieve indicators of independence (e.g., housing, employment), rather than specifically aiming to improve health outcomes, which may account for these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, after engagement in the interventions, the majority of care-leavers achieved housing stability, reported high rates of enrolment or motivation to enrol in further education, and gained access to financial payments. These findings are consistent with previous reviews of international evidence that found transitional support interventions for care-leavers to be most effective in improving outcomes associated with independent living (Heerde et al, 2018;Woodgate et al, 2017). These programmes are effective in providing coordinated support and assisting care-leavers to overcome the barriers to gaining stable housing, continue or finish education, obtain and maintain employment, and increase access to financial stability, which allows them to adequately prepare for and achieve independence.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The manuscript was directly evaluated for inclusion in cases where the title and abstract did not provide sufficient information. The original terms and concepts utilized by the primary authors of literature reviewed remain intact whenever possible to ensure accurate representation of the various outcomes 16,17 .…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%